Shortened left ventricular filling time in dilated cardiomyopathy: additional effects on heart rate variability?. Issue 4 (April 1993) - Mbaissouroum, M; O'Sullivan, C; Brecker, S J; Xiao, H B; Gibson, D G
Abstract : OBJECTIVE--To assess possible mechanical influences underlying the reduced heart rate variability in patients with dilated cardiomyopathy. DESIGN--Comparison of standard non-spectral indices of heart rate variability with echocardiographic Doppler measures of left ventricular function in patients and normal controls. PATIENTS--20 patients with dilated cardiomyopathy and 15 normal subjects of similar ages were studied. METHODS--Standard non-spectral indices of heart rate variability were measured over 24 hours. These were correlated with left ventricular cavity size, shortening fraction, and isovolumic relaxation time measured by M mode echocardiography, and the duration of functional mitral regurgitation and left ventricular filling time assessed by continuous wave Doppler. RESULTS--Mean RR interval and estimates of short term variability (root mean square difference of successive RR intervals, proportion of adjacent RR intervals > 50 ms different, and SD indices) were not different from normal. The overall mean (SD) of the RR interval (65 (35)), and SD of five minute mean RR intervals (55 (30)), however, were reduced compared with normal values (115 (40) and 105 (45); p < 0.01 for both). Neither correlated with left ventricular cavity size or shortening fraction, but both were strongly related to left ventricular filling time (coefficient of variation, r = 0.82 and r = 0.81 respectively). Correlation persisted when the SD was corrected for RR interval (r = 0.69) although this correlation was not found in the controls. In individual patients, the difference between RR interval at the time of echo and minimum value during the 24 hours, a measure of ability to increase heart rate, also correlated closely with filling time (r = 0.92). CONCLUSION--As the duration of functional mitral regurgitation is effectively fixed, its presence can limit the time available for left ventricular filling in dilated cardiomyopathy when heart rate is high. This may become the mechanism by which maximum heart rate is set, becoming fixed to optimise cardiac output. This manifestation of dilated cardiomyopathy may be an important factor in reduction of heart rate variability in these patients.